Performance dynamics of pdc cutters used in breaking ductile brittle rock (Nexo Revista Científica, 2021)
The widespread application of cutting - chipping action bits with PDC cutters is held back due to the intense chipping and breakage of the latter. This article presents the results of bench-scale tests conducted to determine the values of three mutually perpendicular components of the load on sharp-edged and beveled rock-breaking cutters of 13.5 mm in diameter as well as the dynamic-response factors and mean square deviations (MSD) of these components. The forces change in time by leaps, which reflects the rock fracturing under the cutter. The MSD accepted as per-cycle amplitude is four times as low on average as the mean axial force; when a sharp-edged and a beveled cutter is used, the MSD is by 150 to 300 and by 300 to 500 % lower than the mean circumferential force.